2017
DOI: 10.1063/1.4995991
|View full text |Cite
|
Sign up to set email alerts
|

Broadband conversion of microwaves into propagating spin waves in patterned magnetic structures

Abstract: We have used time-resolved scanning Kerr microscopy (TRSKM) and micromagnetic simulations to demonstrate that, when driven by spatially uniform microwave field, the edges of patterned magnetic samples represent both efficient and highly tunable sources of propagating spin waves. The excitation is due to the local enhancement of the resonance frequency induced by the non-uniform dynamic demagnetizing field generated by precessing magnetization aligned with the edges. Our findings represent a crucial step forwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…2(a)), in accordance with the analytical model for spin waves in a Damon-Eshbach configuration from [34], which takes into account the finiteness of the element. This is also consistent with previous results where the edges act as spin wave emitters [12]. In thicker disks ( Fig.…”
Section: A Dispersion Characterizationsupporting
confidence: 93%
“…2(a)), in accordance with the analytical model for spin waves in a Damon-Eshbach configuration from [34], which takes into account the finiteness of the element. This is also consistent with previous results where the edges act as spin wave emitters [12]. In thicker disks ( Fig.…”
Section: A Dispersion Characterizationsupporting
confidence: 93%
“…It has been shown that local magnetic formations such as domain walls [45][46][47], edge bound demagnetizing fields [33,48,49], or vortices [23,24,50] can function as spin wave emitters offering effective "antenna" widths well below 200 nm. A major advantage of this approach is that the devices providing such formations are a lot larger than these effective widths.…”
Section: Resultsmentioning
confidence: 99%
“…For the same reason, no spin-wave emission is possible if the source term = (14) becomes equal to zero for any other reason. Depending on the problem, the local microwave susceptibility tensorsχ A(B) in the vicinity of the interface can be calculated analytically [23] or from micromagnetic simulations [22,24]. The most efficient emission is expected when the source term is strongest.…”
Section: A General Properties Of the Inhomogeneous Boundary Conditionsmentioning
confidence: 99%